2019
DOI: 10.1112/blms.12238
|View full text |Cite
|
Sign up to set email alerts
|

The canonical Einstein metric on G2 is dynamically unstable under the Ricci flow

Abstract: In this note, we show that the bi‐invariant Einstein metric on the compact Lie group G2 is dynamically unstable as a fixed point of the Ricci flow. This completes the stability analysis for the bi‐invariant metrics on the compact, connected, simple Lie groups. Interestingly, G2 is the only unstable exceptional group.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Finally, we note that the bi-invariant metric on the compact Lie group G 2 is known to admit infinitesimal solitonic deformations [4]. In [10], the second author demonstrated that there exist deformations that are not integrable to second order and hence the Einstein metric is dynamically unstable. It would be interesting to extend this analysis to characterise precisely which solitonic deformations are not integrable.…”
Section: 2mentioning
confidence: 90%
“…Finally, we note that the bi-invariant metric on the compact Lie group G 2 is known to admit infinitesimal solitonic deformations [4]. In [10], the second author demonstrated that there exist deformations that are not integrable to second order and hence the Einstein metric is dynamically unstable. It would be interesting to extend this analysis to characterise precisely which solitonic deformations are not integrable.…”
Section: 2mentioning
confidence: 90%
“…Since the operator C is non-negative we get that σ " 0 for λ " 1, so H 1 " 0. Further on the algebraic constraints on σ lead to C ρbπ 1 σ " pλ ´4qpλ ´2qσ according to (15). Since C ρbπ 1 is non-negative σ " 0 for λ " 3 and σ is sup2q-invariant w.r.t.…”
Section: Infinitesimal Einstein and G 2 Deformationsmentioning
confidence: 99%